2020
DOI: 10.1080/15412555.2020.1815182
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in COPD: An Overview by Topics

Abstract: COPD is a major cause of morbidity and mortality worldwide and carries a huge and growing economic and social burden. Telemedicine might allow the care of patients with limited access to health services and improve their self-management. During the COVID-19 pandemic, patient's safety represents one of the main reasons why we might use these tools to manage our patients. The authors conducted a literature search in MEDLINE database. The retrieval form of the Medical Subject Headings (Mesh) was ((Telemedicine OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 65 publications
1
38
0
10
Order By: Relevance
“…This is due to the benefits of TH in detecting COPD deterioration in early stages and minimizing hospital readmission due to exacerbations. Moreover, some evidence found that offering TH interventions to people with COPD seems to be an opportunity to provide quality healthcare and to minimize unnecessary hospitalization [ 61 , 62 ]. A patient’s smoking history was identified as an additional explanatory factor to increase TH acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the benefits of TH in detecting COPD deterioration in early stages and minimizing hospital readmission due to exacerbations. Moreover, some evidence found that offering TH interventions to people with COPD seems to be an opportunity to provide quality healthcare and to minimize unnecessary hospitalization [ 61 , 62 ]. A patient’s smoking history was identified as an additional explanatory factor to increase TH acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physical and psychological disabilities of CRF have repercussions leading to a deterioration in quality of life and loss of autonomy (difficulty to move about and/or the need of assistance) (35). This underlines the need for tailored solutions with an extension of public coverage to a subset of OSAS cases and greater use of telemedicine to preserve the continuity of care for CRF patients (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…A reason for this mediating effect might be that telemonitoring is dependent on behavioral change in the patient and healthcare provider. It is important for patients to follow the monitoring instruction and for healthcare providers to use the results of the monitoring in their management, and using telehealth to deliver education can empower patients by giving them greater insight and the tools to manage their disease [10]. Bonnevie et al [21] showed that interventions with automated feedback, representing a form of patient education, improved long-term adherence to home-based exercise therapy.…”
Section: Telemonitoring and Patient Educationmentioning
confidence: 99%
“…It allows patients to monitor their symptoms and physical parameters at home, share the data with healthcare providers and receive tailored treatment strategies based on that information. In this way, technology can support healthcare providers to deliver personalized disease management and more frequent symptom monitoring without the need for clinical visits or physical on-site assessments [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation